Online lessons. - Isaacs, Lindsay (American City & County, 2003)
The writer discusses how web-based courses are providing opportunities for federal government, local government, and private company employees to improve their skills without attending classes. According to a report by the American Society for Training and Development, the proportion of training delivered via computer increased among all members from 8.8 percent of total training hours in 2000 to 10.5 percent in 2001. The flexibility of online training is attractive to many organizations, but there are some question about whether online courses train employees as well as traditional courses. That is one reason why some local governments are using online courses to supplement, rather than replace, traditional training sessions.